2012
DOI: 10.17221/230/2012-pse
|View full text |Cite
|
Sign up to set email alerts
|

Changes of three organic acids in the process of Cd and Pb phytoextraction by Helianthus annuus L.

Abstract: In the present study, sunflower was used to enrich the cadmium (Cd) and lead (Pb) in sand culture, and the changes of metals uptake, organic acids, pH, and redox potential were investigated. Results showed that the Cd and Pb accumulation was dissimilar in treatments. In single treatments of Cd or Pb, the amount of glutaric and lactic acids decreased with concentrations; the secretion of glutaric and glycolic acids in 5 mg/L Cd treatments were the highest at the 90 th day. In the mixed treatments of Cd and Pb, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
1
2
0
2
Order By: Relevance
“…Moreover, the existence of Cd/Pb ions inhibited the accumulations of Pb/Cd in our study. This finding is in agreement with Guo et al [21] and Niu et al [39], who reported that 5 and 10 mg•kg −1 Cd increased the bioavailability of Pb ions in soil. Besides, studies have shown that the interaction of cadmium with lead or zinc at equimolar concentrations can lower the toxicity of cadmium in plants [40].…”
Section: The Bioaccumulation Of Cadmium and Leadsupporting
confidence: 93%
“…Moreover, the existence of Cd/Pb ions inhibited the accumulations of Pb/Cd in our study. This finding is in agreement with Guo et al [21] and Niu et al [39], who reported that 5 and 10 mg•kg −1 Cd increased the bioavailability of Pb ions in soil. Besides, studies have shown that the interaction of cadmium with lead or zinc at equimolar concentrations can lower the toxicity of cadmium in plants [40].…”
Section: The Bioaccumulation Of Cadmium and Leadsupporting
confidence: 93%
“…5 ), which might be due to the stimulatory effects and adaptive response of plants to their surrounding environments ( Costantini, Metcalfe & Monaghan, 2010 ; Jia et al, 2013 ). Previous research has demonstrated plant growth inhibition when the soil Pb concentration is high, possibly due to the adsorption saturation of Pb by the cell wall, leading to more mobile Pb reaching the protoplasm ( Niu et al, 2012 ; Zhou et al, 2017 ). Bahram et al ( Gholinejad et al, 2020 ) found that the content of photosynthetic pigments, biomass, seed vitality and emergence rate of non-tolerant ryegrass plants were negatively affected by a soil Pb concentration of 250 mg kg −1 .…”
Section: Discussionmentioning
confidence: 99%
“…[52][53][54] Uma variedade de trabalhos tem demonstrado que muitas espécies exsudam AO para aumentar a absorção de elementos tóxicos, tais como Cd e Cr, com papel importante na fitorremediação de solos contaminados. [53][54][55] Em todas essas abordagens destacam-se os ácidos aspártico, cítrico, málico e oxálico. Por último, alguns AO, como os ácidos aspártico, málico e tartárico têm papel crucial no valor nutritivo de algumas espécies.…”
Section: Determinação Dos Ao Em Folhas De Azevém Anualunclassified
“…11,60 A identificação de três AO, a saber, cítrico, málico e aspártico em folhas de azevém anual pode ser uma possível explicação da espécie ser capaz de acumular em sua estrutura teores mais elevados de metais do que as exigências nutricionais e inclusive de elementos tóxicos, como o Cr. [55][56][57] Em termos de Kest, o Pb teoricamente deveria ter sido absorvido em maior quantidade pela planta, ao invés do Cr, que forma complexos estáveis apenas com o ácido acético e oxálico, que não foram identificados na espécie, conforme Tabela 10. Alguns autores citam a competição iônica em termos de absorção radicular e posterior translocação do metal na planta.…”
Section: Determinação Dos Ao Em Folhas De Azevém Anualunclassified